Evaluative Diversity and the Board. Issue 146 (July 2016) - Santos‐Lang, Chris
Abstract : In the second article of this issue of Board Leadership addressing the board's job of creating both plurality and unity, Chris Santos‐Lang introduces the concept of evaluative diversity.